1997
DOI: 10.1037/0022-0167.44.2.189
|View full text |Cite
|
Sign up to set email alerts
|

The Missouri Psychoanalytic Counseling Research Project: Relation of changes in counseling process to client outcomes.

Abstract: A short-term psychoanalytic counseling model was used to identify process dimensions and client outcomes. Six counselors saw 16 clients over the course of 2 semesters. Clients responded to measures at pre-and posttest and after each session, and counselors filled out measures following each session. Sessions were audio-and videotaped and viewed by trained raters. P-technique factor analysis identified 4 dimensions: Psychoanalytic Technique, Working Alliance, Client Resistance, and Client Transference. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
1
7

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(92 citation statements)
references
References 67 publications
5
79
1
7
Order By: Relevance
“…More recently, however, researchers have also examined how different patterns of alliance development relate to outcome. For example, several studies have demonstrated that U-shaped alliance trajectory is associated with patient improvement (Horvath & Marx 1991;Kivlighan & Shaughnessy, 2000;Patton, Kivlighan, & Multon, 1997). This pattern has been hypothesized to reflect the presence of a difficult, but productive working-through phase in the middle of treatment that manifests as lower alliance ratings.…”
Section: Predictors Of Alliance Development Over Timementioning
confidence: 99%
“…More recently, however, researchers have also examined how different patterns of alliance development relate to outcome. For example, several studies have demonstrated that U-shaped alliance trajectory is associated with patient improvement (Horvath & Marx 1991;Kivlighan & Shaughnessy, 2000;Patton, Kivlighan, & Multon, 1997). This pattern has been hypothesized to reflect the presence of a difficult, but productive working-through phase in the middle of treatment that manifests as lower alliance ratings.…”
Section: Predictors Of Alliance Development Over Timementioning
confidence: 99%
“…Several longitudinal studies (e.g., Golden & Robbins, 1990;Patton, Kivlighan, & Multon, 1997;Kivlighan & Shaughnessy, 2000;Stiles et al, 2004) tracked alliance development using different statistical methods and identified distinct patterns associated with the alliance evolution across time. In general, the aforementioned studies suggest that positive linear increase and quadratic high-low-high patterns of alliance development are related to good therapeutic outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Cependant cette approche a été utilisée dans la littérature sur le conseil pour identifier différents types de processus à l'oeuvre en psychothérapie (Patton, Kivlighan & Multon, 1997 ;Russel, Bryant & Estrada, 1996) et les variations dans les patterns de réponses émotionnelles de beauxenfants à l'intérieur de leurs familles, dans le temps (Corneal & Nesselroade, 1994) 1 . Il est évident que cette technique pourrait être utile dans l'étude de questions concrètes sur les processus du conseil en orientation.…”
Section: La Distinction « Traits-états » Et Les « P-techniques » 34unclassified